THE INFLUENCE OF LEARNING MOTIVATION AND ORGANIZATIONAL INVOLVEMENT ON ACADEMIC PROCRASTINATION THROUGH TIME MANAGEMENT - Fatoni, Arif; Dialoni, Diah; Munawaroh, Munawaroh; Sugiarto, Apprillia Anggraeni; Kurniawan, Dandi (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2024)
Schools are responsible for teaching students to be active in creative thinking, innovation, and diligent in completing their tasks. The purpose of this research is to explain (1) the influence of learning motivation on academic procrastination, (2) the influence of organizational involvement on academic procrastination, (3) the influence of time management on academic procrastination, (4) the influence of learning motivation on academic procrastination through time management; and (5) the influence of student involvement on academic procrastination through time management. This study employs a quantitative research approach, with data collected through observation, interviews, documentation, and questionnaires. The population of this research consists of 461 students from public high schools in Jombang Regency. The total sample size was determined using Slovin's formula, resulting in a sample of 82 students. In the course of this research, Partial Least Squares (PLS) were used as a technique for data analysis. The results indicate that learning motivation and organizational involvement affect time management, with a value of 0.134, meaning that the variables of learning motivation and organizational involvement can influence the time management variable by 13.4%. The R-squared value for the influence of learning motivation, organizational involvement, and time management on academic procrastination is 0.256, indicating that these variables can influence academic procrastination by 25.6%. Thus, this shows that learning motivation and organizational involvement affect academic procrastination through time management. Klasifikasi Jel: M21;J24 Kata Kunci: Motivasi Belajar, Keaktifan Berorganisas, Prokrastinasi Akademik, Manajemen Waktu